2015
DOI: 10.1248/bpb.b15-00128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anti-tumor Effects of Selective Serotonin Reuptake Inhibitors as Well as Serotonin and Norepinephrine Reuptake Inhibitors in Human Hepatocellular Carcinoma Cells

Abstract: The anti-tumor effects of selective serotonin reuptake inhibitors (SSRIs) and serotonin and norepinephrine reuptake inhibitors (SNRIs) on several types of cancer cells have been reported. However, comparison of the anti-tumor effects of these drugs on human hepatocellular carcinoma (HepG2) cells has not been studied. We compared the anti-tumor effects of four SSRIs and two SNRIs on HepG2 cells. SSRIs and duloxetine dose-dependently decreased cell viability. Milnacipran had no effect on cell viability. The half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
(24 reference statements)
1
38
1
Order By: Relevance
“…15 Kuwahara et al showed the apoptotic effect of paroxetine in human HepG2 hepatocellular carcinoma cells. 9 Consistent with the findings of these studies, our findings revealed the capacity of paroxetine to cause cell growth inhibition, cell death induction, and anticancer effect in HT29-xenografted mice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…15 Kuwahara et al showed the apoptotic effect of paroxetine in human HepG2 hepatocellular carcinoma cells. 9 Consistent with the findings of these studies, our findings revealed the capacity of paroxetine to cause cell growth inhibition, cell death induction, and anticancer effect in HT29-xenografted mice.…”
Section: Discussionsupporting
confidence: 91%
“…Several classes of antidepressants, including tricyclic antidepressants (TCAs), serotonin‐norepinephrine reuptake inhibitors, and selective serotonin‐reuptake inhibitors (SSRIs), are available. Recent studies have shown that certain TCAs and SSRIs exhibit potent anticancer activities as well as psychotropic effects . In a previous epidemiological study, daily intake of SSRI was shown to reduce the risk of CRC, whereas no protective effect was found for TCAs .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, comparison of anti-tumor effects of SSRIs and SNRIs on HepG2 cells has not been studied. Here, we compared the anti-tumor effects of four SSRIs (escitalopram, fluvoxamine, paroxetine, sertraline) and two SNRIs (duloxetine, milnacipran) on HepG2 cells [48] . Bernhard Svejda et al mentioned that fibrosis is a cardinal feature of small intestinal neuroendocrine tumors (SI-NETs) both in local peritumoral tissue and systemic sites (cardiac).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, common therapies for stress and anxiety disorders, such as benzodiazepines and SSRIs, also inhibit proliferation and migration of cancer cells in vitro [43-45]. Studies using in vivo models have confirmed that stress enhances tumor growth and that stress reduction, either via behavioral or pharmacological means, retards disease progression [39, 46, 47].…”
Section: Neuroactive Molecules and Cancermentioning
confidence: 99%